Confirming the recessive inheritance of SCN1B mutations in developmental epileptic encephalopathy. Issue 3 (19th April 2017) - Ramadan, W.; Patel, N.; Anazi, S.; Kentab, A.Y.; Bashiri, F.A.; Hamad, M.H.; Jad, L.; Salih, M.A.; Alsaif, H.; Hashem, M.; Faqeih, E.; Shamseddin, H.E.; et al.
Abstract : Dominant SCN1B mutations are known to cause several epilepsy syndromes in humans. Only 2 epilepsy patients to date have been reported to have recessive mutations in SCN1B as the likely cause of their phenotype. Here, we confirm the recessive inheritance of 2 novel SCN1B mutations in 5 children from 3 families with developmental epileptic encephalopathy. The recessive inheritance and early death in these patients is consistent with the Dravet‐like phenotype observed in Scn1b −/− mice. The 'negative' clinical exome in one of these families highlights the need to consider recessive mutations in the interpretation of variants in typically dominant genes. Abstract :